c.2 - Naval, T.R. (New Delhi, 2001)
The book explores the history of practice of untouchability and commission of atrocities on the Scheduled Castes and Scheduled Tribes; analyses the origin of caste disabilities, problems of atrocities faced by them over centuries; traces out and determines the causes and factors responsible for its origin and continuation of atrocities on the Scheduled Castes and Scheduled Tribes; deals with various aspects of atrocities such as personal, physical, economical, educational, social and grave aspect; explicates provisions of the Act and the term Scheduled Castes. It also contains existing enactment on the subject to counter the atrocities as also protection against various acts of atrocities on Scheduled Castes and Scheduled Tribes. This book seeks to serve the purpose as reference. book on the subject.
Keywords: Atrocities